Assessment of the effect of low-cost negative pressure dressing on wound healing - Lingayat, Maruti B.; Kawedia, Abhay M.; Gathani, Hitarth J.; Baria, Karan; Patil, Swapnilkumar (International Journal of Research in Orthopaedics, 2023)
Background: Wound care is a priority element in the management of grade 3 compound fractures and has traditionally relied on the use of dressing products (gauze, foam dressings, alginates, and hydrocolloids) and manual debridement. Paving the way to the future, there are now several alternative therapies, of which negative pressure wound therapy (NPWT) is an emerging treatment. Negative suction dressing has been proven to be superior in wound healing and is faster compared with regular dressing using gauze, hydrocolloids, and local debridement. It leads to faster rates of skin cover spontaneously or with surgical procedures like skin graft and flaps, eventually resulting in early internal fixation of fractured bones, if any. The present study was designed to assess the effect of the negative pressure dressing technique on wound healing and to compare its effect with that of the conventional dressing technique. Methods: The study was a double-blind randomized control trial conducted after ethics approval. A case record form was used for data collection after obtaining the participants’ informed consent, and a total of 120 patients participated in the study. Results: Low-cost negative pressure dressing has an effect on general conditions, fever, hyperemia, and irregular margins. It was observed to increase granulation tissue formation and decrease pus/serous discharge and was associated with a decreased number of hospital visits due to early healing compared with normal dressing. Conclusions: The low-cost negative dressing technique was effective in healing wounds in type III open fractures and was associated with early recovery compared with the normal dressing technique.